From Environmental Clicktivism to Trash Cleanup : New Initiative of Instagram Account @Pandawaragroup - Erika, Desy; Alawi, Akhmad Roqi (Universitas Multimedia Nusantara, 2024)
Environmental awareness movements on social media are often limited to